2016
DOI: 10.1093/jac/dkw448
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of p110δ subunit of PI3K confers protection against experimental leishmaniasis

Abstract: Prophylactic and therapeutic administration of p110δ pharmacological inhibitors significantly reduced cutaneous lesion (in CL) and parasite burdens (in VL and CL) in the spleens, livers and footpads of infected mice. The reduction in parasite burden was associated with a concomitant reduction in Treg numbers and cytokine production by liver, spleen and lymph node cells. Combined low-dose CAL-101 and amphotericin B therapy caused complete clearance of parasites in mice infected with L. donovani CONCLUSIONS: Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 47 publications
1
49
0
Order By: Relevance
“…This could further promote MAPK and NF-κB activity ( Vishwakarma et al, 2018 ). A recent study by Khadem et al (2017) , showed that administration of PI3K p110δ inhibitors CAL-101 and IC87114 resulted in a decrease in parasitic burden in both a CL and VL murine model. This result was accompanied by increased cytokine production in the spleen, livers and footpads of infected mice.…”
Section: Host-targeted Therapeutics and Approaches For Treatment Of Lmentioning
confidence: 99%
See 1 more Smart Citation
“…This could further promote MAPK and NF-κB activity ( Vishwakarma et al, 2018 ). A recent study by Khadem et al (2017) , showed that administration of PI3K p110δ inhibitors CAL-101 and IC87114 resulted in a decrease in parasitic burden in both a CL and VL murine model. This result was accompanied by increased cytokine production in the spleen, livers and footpads of infected mice.…”
Section: Host-targeted Therapeutics and Approaches For Treatment Of Lmentioning
confidence: 99%
“…This result was accompanied by increased cytokine production in the spleen, livers and footpads of infected mice. The authors suggest the use of these inhibitors along with amphotericin B for even better outcomes ( Khadem et al, 2017 ).…”
Section: Host-targeted Therapeutics and Approaches For Treatment Of Lmentioning
confidence: 99%
“…Therapeutic administrations (after one or two weeks) of idelalisib (0.05 mg per mouse) have been shown to significantly ( p <0.05) lower parasite burden in the spleens and livers of L. donovani ‐infected mice. In addition, treatment of infected mice with idelalisib (0.05 mg per mouse) and amphotericin B (0.1 mg kg −1 ) also leads to a complete clearance of parasites both in spleen and in the liver . The decrease in parasite burden was associated with a concomitant reduction in regulatory T cell numbers and cytokine production by the liver, spleen and lymph node cells, as the direct growth of L. donovani promastigotes in axenic was not affected by any concentration tested of idelalisib or IC87114.…”
Section: Human Kinase Inhibitor Repurposing In Trypanosomatidsmentioning
confidence: 91%
“…Two mammalian atypical kinase inhibitors, idelalisib, a p110δ‐specific inhibitor approved for treatment of different B cell malignancies, and IC87114, a mixed PI3K inhibitor, have been evaluated in Leishmania (Figure ) . Prophylactic administrations of idelalisib (0.05 mg per mouse) or IC87114 (0.5 mg per mouse), have been shown to significantly ( p <0.01) decrease lesion size in CL and parasite burdens in VL and CL in the spleen and liver of L. donovani ‐infected mice, and footpad of L. major ‐infected mice.…”
Section: Human Kinase Inhibitor Repurposing In Trypanosomatidsmentioning
confidence: 99%
“…Another signaling pathway inhibitor, AS-605240 (PI3K gamma inhibitor) has shown to be as efficacious as sodium stibogluconate (SSG) in the treating of L. mexicana infection [92]. Similarly, another PI3K inhibitor CAL-101 and IC87114 are known to effectively reduce parasitic burden by reducing the B-cells and regulatory T-cells populations [93,94]. Another tyrosine kinase inhibitor, ibrutinib has been shown to treat leishmaniasis by triggering T H 1-polarized IFN-γ production [95].…”
Section: Immunomodulatorsmentioning
confidence: 99%